Impact of afforestation on coastal aquifer recharge : Case study: eastern coast of the Province of Buenos Aires, Argentina - Rodrigues Capítulo, Leandro (2018)
The efects of aforestation on groundwater recharge—which is the only source of drinking water supply in the Pinamar District (Partido de Pinamar), located on the eastern coast of the Province of Buenos Aires, Argentina—are analysed. The study area is characterised by a sand-dune barrier parallel to the coast, where freshwater lenses accumulate. These are bounded to the west by the brackish water of the continental plain and to the east by the seawater. Soil texture makes it possible to infer the infltration capacity. Methods associated with groundwater table fuctuations, hydrodynamics, hydrochemistry and the characteristics of stable isotopes (²H and ¹⁸O) in groundwater were used. In order to confrm the results, daily water balances were carried out. Recharge variations were quantifed based on periodic groundwater table records and water balances. A decrease in recharge was verifed in forested areas with respect to non-forested areas (bare soil). The groundwater fow (hydraulic gradients), the electrical conductivity of groundwater and the fractionation of stable isotopes indicate that the higher evapotranspiration in areas with tree cover leads to a decrease in water surplus and in the possibilities for groundwater table recharge. The efects of aforestation on recharge and, therefore, on good-quality shallow groundwater reserves constitute a key element in planning the sustainable use of the water resources.